Electroacupuncture for post-stroke depression: a systematic review and meta-analysis of randomized controlled trials - Zhang, Zhihui; Xue, Kaiyang; Li, Hongying; Yan, Mingxi; Cui, Jin (Frontiers in Neurology, 2025)
Background and purposeElectroacupuncture (EA) is a non-pharmacological therapy within Traditional Chinese Medicine (TCM) for treating depressive disorders. This meta-analysis aims to evaluate the efficacy of EA in treating post-stroke depression (PSD).MethodsSeven electronic databases were searched up to May 31, 2025, and randomized controlled trials (RCTs) on EA for PSD were screened. After two reviewers independently screened the literature, extracted data, and assessed the risk of bias in included studies, meta-analysis was performed using RevMan software (version 5.4) and Stata/MP software (version 17.0).ResultsEleven studies involving 853 participants were included. EA significantly reduced Hamilton Depression Rating Scale (HAMD) scores (mean difference [MD] = −3.68, 95% confidence interval [CI]: −5.78 to −1.59, p = 0.0006). Additionally, EA significantly reduced Self-Rating Depression Scale (SDS) scores (MD = −3.08, 95% CI: −5.94 to −0.21, p < 0.0001) and National Institutes of Health Stroke Scale (NIHSS) scores (MD = −1.85, 95% CI: −2.93 to −0.77, p = 0.0008). Subgroup analysis demonstrated that EA significantly increased effective rates over simple acupuncture (RR = 1.38, 95% CI: 1.21 to 1.59, p < 0.0001), regional cerebral blood flow (rCBF) (MD = 24.21, 95% CI: 13.64 to 34.78, p < 0.0001), and plasma 5-hydroxytryptamine (5-HT) levels (MD = 16.83, 95% CI: 12.75 to 20.91, p < 0.0001). EA also significantly improved: stroke scores (SS) (MD = 2.56, 95% CI: 1.13 to 3.99, p = 0.0005), World Health Organization Quality of Life-BREF (WHOQOL-BREF) scores (MD = 1.85, 95% CI: 0.72 to 2.98, p < 0.0001), and Activities of Daily Living (ADL) scale scores (MD = 23.45, 95% CI: 17.38 to 29.52, p < 0.0001).ConclusionEA may be an effective therapeutic approach for the comprehensive management of PSD. The observed clinical benefits of EA, including improvements in depression scale scores and quality of life metrics, may contribute to its potential utility in PSD management. However, the certainty of this evidence is limited by the low methodological quality of the available primary studies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/search, identifier CRD420251055828.